2008
DOI: 10.1158/0008-5472.can-08-0153
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cellular Immune Responses against PAX5, a Novel Target for Cancer Immunotherapy

Abstract: PAX5 is a member of the PAX family of developmental transcription factors with an important role in B-cell development. Its expression in normal adult tissue is limited to the hemopoietic system, but it is aberrantly expressed in a number of solid cancers and leukemias where it functions as an oncogene. We therefore hypothesized that anti-PAX5 immune responses could be used to target a number of malignancies without significant toxicity. We screened PAX5 peptides for the ability to bind HLA-A2 and identified a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In addition, we reasoned that opsonized Daudi cells could, in this model, serve as a source of TAA for processing and presentation on gd T MHC to other T cells in a rituximab-dependent manner. To test this, we investigated cross-presentation of PAX5 Ag, a nuclear transcription factor expressed in B lineage cancer cells including Daudi (22,23), by gd T MHC class I. We have previously described a CD8 CTL clone specific for the PAX5 peptide sequence TLPGYPPHV and restricted to HLA-A*0201 (22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we reasoned that opsonized Daudi cells could, in this model, serve as a source of TAA for processing and presentation on gd T MHC to other T cells in a rituximab-dependent manner. To test this, we investigated cross-presentation of PAX5 Ag, a nuclear transcription factor expressed in B lineage cancer cells including Daudi (22,23), by gd T MHC class I. We have previously described a CD8 CTL clone specific for the PAX5 peptide sequence TLPGYPPHV and restricted to HLA-A*0201 (22).…”
Section: Resultsmentioning
confidence: 99%
“…High-avidity CTL clones raised against HLA-A2-restricted epitopes, TLPGYPPHV derived from PAX5 and VLDGLDVLL derived from PRAME, have been previously described (21,22). To generate Ag-specific but Ag-inexperienced T cells, we transduced healthy donor PBMCs with a retrovirus expressing MART-1 TCR (containing a Vb12 chain) specific to an HLA-A*0201-restricted epitope, M26-35 (ELAGIGILTV).…”
Section: Ab Ctl Clones and Ab T Cells Transduction With A Mart-1 Tcr-mentioning
confidence: 99%
“…It was recently reported that a splice variant of LCP2 resulted in severe immune dysregulation ( 32 ). The PAX5 encoded transcription factor is a PAX family member which plays important roles in B-cell development ( 33 ). Via the chromatin immunoprecipitation (ChIP) technique, PAX5 was found to regulate target genes by directly activating chromatin at the promoter or enhancer region, and PAX5 -activated targets are crucial regulators involved in B-cell signaling, migration and immune function ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the antigen specificity of individual memory CD8+ and CD4+ T cell clones among candidate antigens with known relevance in acute leukemias, e.g. WT-1 [43], PRAME [44], PAX5 [45], and their in vitro reactivity with autologous leukemic blasts will be determined. Together, these insights can contribute to the development of effective immunotherapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%